Social innovation, entrepreneurship, and sustainability - Carvalho, João M. S. (2022)
This chapter provides a summarized and objective review over the relationships among innovation, social innovation, entrepreneurship, social entrepreneurship, new business models (NBM), value proposition and sustainability (economic, social, ecological, and psychological). A study has been done in Porto region through interviews with 13 social innovators and entrepreneurs to evaluate those relationships. The conceptual base for the analysis presented in this chapter is tetrad-value theory. It has been concluded that market-oriented social innovation has a crucial role in the social entrepreneurship development. Moreover, these NBM should be adjusted to population needs towards societal well-being, by combining creation of shared value, co-creation of value, and multiple value creation. Thus, a transformational value proposition contributes to economic, social, ecological, and psychological sustainability, and consequently to human, social and territorial development.